2008
DOI: 10.1016/j.ajog.2007.07.038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of esterases on 17α-hydroxyprogesterone caproate

Abstract: Objectives-The aim of this investigation is to determine whether 17α-hydroxyprogesterone caproate is hydrolyzed, in vitro, to 17α-hydroxyprogesterone and caproate. Conclusion-17α-Hydroxyprogesterone caproate is not hydrolyzed in vitro by the esterase enzymes present in human plasma, liver, preterm or term placenta. Study design-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This data is in agreement with recent reports on the lack of 17HPC hydrolysis by S9 fractions obtained from term 2,8 and preterm placentas 2 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This data is in agreement with recent reports on the lack of 17HPC hydrolysis by S9 fractions obtained from term 2,8 and preterm placentas 2 .…”
Section: Resultssupporting
confidence: 94%
“…If a prodrug, then there are at least two possible pathways for its metabolism (Figure 1): First, hydrolysis of the ester bond in 17-HPC by plasma or tissue esterases and thus the formation of 17α-hydroxyprogesterone (17HP) and caproate; Second, the oxidation or conjugation of 17HPC by cytochrome P450 isozymes or other enzymes, respectively. Recent investigations in our laboratory revealed that 17HPC is not hydrolyzed in vitro by either human plasma or tissue-derived preparations obtained from the liver, term and preterm placenta 2 . However, the absence of 17HPC hydrolysis in vitro does not exclude that it could be hydrolyzed in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…A recent investigation in our laboratory revealed that 17-HPC was not hydrolyzed in vitro by human plasma and homogenates of human livers and placental trophoblast tissue [11]. Moreover, the drug was not hydrolyzed during its transfer across the dually perfused placental lobule but an unknown metabolite of 17-HPC was formed and partially identified [12].…”
Section: Discussionmentioning
confidence: 97%
“…Recent investigations in this laboratory on the in vitro hydrolysis of 17-HPC, radiolabeled in the progesterone [ 3 H] and caproate [ 14 C] revealed that the drug is neither hydrolyzed by human plasma, nor homogenates of human liver, term and preterm placentas [11]. Subsequent investigations on human placental transfer, metabolism and distribution of the radiolabeled 17-α-hydroxy-[ 3 H] progesterone [ 14 C] caproate utilizing dual perfused placental lobule revealed that 17-HPC was transferred to the fetal circuit, metabolized and retained by the placental tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic derivative 17OH-PC is resistant to metabolism by traditional steroid-transforming enzymes, and is thus unlikely to replicate all of the actions of natural progesterone. 17OH-PC is not a prodrug, and is not cleaved to 17 alpha-hydroxyprogesterone,24 a metabolite of progesterone already endogenously produced by the placenta in large amounts 25. The only metabolism observed with 17OH-PC is oxidation by cytochrome P450 3A in hepatocytes to monohydroxy, dihydroxy, and trihydroxy derivatives, with unknown resulting activity 26.…”
Section: Efficacy Of Hydroxyprogesterone Caproatementioning
confidence: 99%